1997
DOI: 10.1021/la960909o
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Micelle-Forming Local Anesthetics into Surface-Adsorbed Films and Micelles of Decylammonium Chloride

Abstract: The incorporation of two micelle-forming local anesthetics, dibucaine hydrochloride (DC·HCl) and tetracaine hydrochloride (TC·HCl), into surface-adsorbed films and micelles formed by decylammonium chloride (DeAC) was studied by measuring the surface tension of aqueous solutions of DeAC−DC·HCl and DeAC−TC·HCl binary mixtures. The quantities of the anesthetics incorporated into the adsorbed film and micelle of DeAC were estimated from the compositions of the anesthetics in the adsorbed film and micelle, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The thinner phase diagram of the DeAC−DC · HCl system than that of the DeAC−TC · HCl system implies that greater quantities of DC · HCl than TC · HCl exist in the mixed micelle. The more hydrophobic DC · HCl than TC · HCl partitions larger quantities into the micelle, and the result correlates with their anesthetic potency . Further, the phase diagrams of both systems showed a slightly distorted shape, especially in the low composition region.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The thinner phase diagram of the DeAC−DC · HCl system than that of the DeAC−TC · HCl system implies that greater quantities of DC · HCl than TC · HCl exist in the mixed micelle. The more hydrophobic DC · HCl than TC · HCl partitions larger quantities into the micelle, and the result correlates with their anesthetic potency . Further, the phase diagrams of both systems showed a slightly distorted shape, especially in the low composition region.…”
Section: Discussionmentioning
confidence: 93%
“…Although decylammonium and local anesthetic cations are weak electrolytes, we assumed in this study that DeAC and the anesthetics are uni-univalent electrolytes on account of their relatively high p K a values, as described previously. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decylammonium chloride (DeAC) was synthesized and purified by the method reported previously. 27 Their purities were confirmed by elemental analysis, and those of DC‚HCl, TC‚HCl, and DeAC were also checked by observing the absence of a minimum on the surface tension vs concentration curves in the vicinity of the critical micelle concentration. The molecular structures of these anesthetics and surfactant are illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 97%
“…Analogous to the present results, it was also found that an abrupt transition occurred close to the pK a of these substances. The pH-dependent surface activity is also interesting from the perspective of the mechanisms of the action of local anesthetics (63,64).…”
Section: Effects Of Lidocaine and Prilocainementioning
confidence: 99%